Kajian Karakteristik Lanskap Umah Pitu Ruang (UPR) Umah Edet Reje Baluntara di Desa Toweren Uken Kecamatan Lut Tawar Kabupaten Aceh Tengah - Yanti, Resi Selvi; Arafat, Pratitou; Wulandari, Elysa (Jurnal Lanskap Indonesia, 2023)
Umah Pitu Ruang(UPR) is a traditional house of the Gayo people, Central Aceh, and one of the cultural heritage of the Gayo tribe which is almost extinct. Much research has been conducted on the architecture of UPR, but research on the landscape characteristics of UPR in Gayo, Central Aceh is still limited. Whereas landscape characteristics are also an important element in studying and identifying UPR. One of UPR that still exists is Umah Edet Reje Baluntara in the village of Toweren Uken. This study aims to determine the characteristics of the landscape at UPR based on the results of interviews, observations, and documentation studies on Umah Edet Reje Baluntara. The results are the identification of landscape character of UPR, the landscape elements on the UPR homegarden, and the function of the outer space of UPR. Based on the results of the study it can be concluded that: The landscape characteristics of UPR Baluntara include macro and micro conditions. Hardscape elements consist of an artificial pond, Mersah, Doyah/Joyah, chicken coop, walkways, and rocks, while the softscape elements are: guava trees, coconut trees, orange groves, herbs, medicinal herbs, and rivers. As for the outdoor function of UPR, it is a space that is used for various types of activities. A study of landscape characteristics can be proposed and used as a reference for the traditional landscape of Gayo Traditional Houses.